Health and Beauty : A Book for Girls - Foley, Elizabeth; Cocker, Edith A. (London : The Health & Cleanliness Council)
1939-10 1939 1930s 27 pages ; illustrations Beauty takes a bath THE body, however well washed it may be one day, is ready to be washed next day, because the skin is always giving off a greasy secretion, even when we are lying quietly in bed. So you must keep the pores open if you want a clear skin free from blackheads and pimples. The best way to do this is, of course, to take a daily bath. Most houses nowadays have a bathroom or at any rate a fixed bath, for great strides have been made in this respect during the last few years by the housing authorities and by private builders. The health value of the bath is always increased if it is followed by a vigorous rubbing with the towel. This rubbing brings a glow to the skin and is health-giving and a real beautifier. It is best that the bath should be neither too hot nor too cold. Cold baths, especially in winter time, are only for those who feel a glow immediately afterwards. If you are blue and shivery after a cold bath, that shows that a cold bath is not good for your heart or your circulation — it is better to have the water just pleasantly hot. The girl living in a boarding house or a club, as many business girls do in these days, may find it at times difficult to fit in her daily bath, but with a little skilful planning it is usually possible to fit in with a timetable. The girl who lives at [illustration] 3 177/5/8/4